Priscilla Mourgues, La poétique du voyage dans le Livre des Merveilles (manuscrit Paris, Bibliothèque nationale de France, fr. 2810) - Priscilla Mourgues (Perspectives Médiévales)
This thesis focuses on the manuscript entitled the Book of Wonders (manuscript Paris, Bibliothèque nationale de France, fr. 2810), which was composed at the beginning of the 15th century and brings together works on the Orient written in the 13th and 14th centuries, some of which were translated by the monk Jean le long d’Ypres. It includes famous texts such as the Devisement du monde by Marco Polo, the Relatio by Odoric de Pordenone, the Travels by Sir John Mandeville and the Fleur des estoires de la terre d’Orient by Hayton, as well as lesser-known texts: Riccold de Monte Croce’s Peregrination, William of Boldensele’s Traitié de l’estat de la Terre sainte et ossy en partie de la terre d’Egippte, the Livre de l’estat du grant Caan, and letters exchanged between the Pope and Christians in Asia. The aim is to study how this manuscript is characterised by a poetics of travel, which unites the texts, however varied they may be, and establishes a particularly rich dialogue between writings and images. The notion of poetics is thus considered in its relationship with literary creation, with aesthetics and also with a form of pleasure in the text. The first part of this work focuses on the collection of different testimonies within a single codex. It proposes an analysis of the manuscript tradition of each text of the Book of Wonders, of the story of the manuscript and its composition, and then of the writing of the travellers’ experience, mixed with inventions, and their desire to transmit a message to their readers. The second part proposes a more formal study of the manuscript, by analysing more specifically its dispositio. The aim is to show how an specific aesthetic of the hidden and the shown is created through the important practice of ellipsis and condensation on the one hand, and, on the other, through a strong rhetoric of ostension. If certain works in the manuscript give an impression of fragmentation, the Book of Wonders undeniably weaves links between the texts and thus creates continuities and exchanges between them. Finally, the third part of this thesis focuses on the notion of entertainment. It considers the manuscript for the pleasure it can provide to the readers, as the traveller-authors have to show ingenuity to tell the unknown and insert micro-narratives, mostly exotic, in their works. The pictures provide an entirely different kind of entertainment through the dialogue they establish with the text.